Quantifying the relationship between physical performance and mental wellbeing in older adults: a field study - Járai, Róbert; Stephens-Sarlós, Erzsébet; Ihász, Ferenc; Bulgay, Celal; Balog, Ádám; Horváth-Pápai, Anna; Alföldi, Zoltán; Tóth, Eliza E.; Somogyi, Angéla; Podstawski, Robert; Szabo, Attila (Frontiers in Aging, 2025)
IntroductionAlthough the relationship between functionality, as reflected in physical performance (PHP), and mental health in older adults has been researched, its strength remains unclear.MethodsThis field study aimed to determine the strength of this relationship in adults aged 60 and above using seven PHP indices and six psychological measures. We individually tested 114 older adults. Objective measures included six PHP indices consisting of the Senior Test and handgrip strength. Subjective measures included resilience, wellbeing, happiness, perceived stress, hopelessness, and life satisfaction.ResultsStructural equation modeling (SEM) revealed two latent constructs: PHP and mental wellbeing (MWB): robust fit (MLR): X2 (75) = 136.28, p < 0.001; CFI = 0.967; TLI = 0.960; RMSEA = 0.066 (90% CI [0.000, 0.128]); SRMR = 0.088. The latent partial correlation between PHP and MWB (adjusted for Age) was φ = 0.46, indicating ∼21% shared variance. The correlation between the two latent factors was moderate (r = 0.46), suggesting that other unassessed factors might account for the relationship.DiscussionBased on objective PHP and subjective MWB measures, these results suggest a modest connection, with the two latent constructs sharing ∼1/5 of their variances. Consequently, further research is needed to identify other factors affecting the studied relationship in older adults. These cross-sectional findings, suggesting a moderate association, should be interpreted with caution. Still, they support recommending physical activity as one component of broader, multi-domain strategies to support the wellbeing of older adults.